A decade of data: Adolescent vaccination in the vaccine safety datalink, 2007 through 2016. Issue 9 (23rd February 2022) - Irving, Stephanie A.; Groom, Holly C.; Dandamudi, Padma; Daley, Matthew F.; Donahue, James G.; Gee, Julianne; Hechter, Rulin; Jackson, Lisa A.; Klein, Nicola P.; Liles, Elizabeth; Myers, Tanya R.; Stokley, Shannon
Highlights: Adolescent vaccine recommendations have expanded and evolved since 2005. The Vaccine Safety Datalink has a robust adolescent population to study vaccination. Vaccination coverage and patterns of concurrent administration were examined. Vaccination rates were comparable to United States estimates. Abstract: Background: Between May 2005 and March 2007, three vaccines were recommended by the Advisory Committee on Immunization Practices for routine use in adolescents in the United States: quadrivalent meningococcal conjugate vaccine (MenACWY), tetanus, diphtheria and acellular pertussis vaccine (Tdap), and human papillomavirus vaccine (HPV). Understanding historical adolescent vaccination patterns may inform future vaccination coverage efforts for these and emerging adolescent vaccines, including COVID-19 vaccines. Methods: This was a descriptive, retrospective cohort study. All vaccines administered to adolescents aged 11 through 18 years in the Vaccine Safety Datalink population between January 1, 2007 and December 31, 2016 were examined. Vaccination coverage was assessed by study year for ≥1 dose Tdap or Td, ≥1 dose Tdap, ≥1 dose MenACWY, ≥1 dose HPV, and ≥3 dose HPV. The proportion of vaccine visits with concurrent vaccination (≥2 vaccines administered at the same visit) was calculated by sex and study year. The most common vaccine combinations administered in the study population were described by sex for two time periods: 2007–2010 and 2011–2016. Results: The number of 11–18-year-olds in the study population averaged 522, 565 males and 503, 112 females per study year. Between January 2007 and December 2016 there were 4, 884, 553 vaccine visits in this population (45% among males). The overall proportion of concurrent vaccine visits among males was 43% (33–61% by study year). Among females, 39% of all vaccine visits included concurrent vaccination (32–48% by study year). Vaccine coverage for Tdap, MenACWY, and 1- and 3-dose HPV increased across the study period. A wide variety of vaccine combinations were administered among both sexes and in both time periods. Conclusions: The high vaccine uptake and multitude of vaccine combinations administered concurrently in the adolescent population of the Vaccine Safety Datalink provide historical patterns with which to compare future adolescent vaccination campaigns.